Factors Causing the Occurrence of Embezzlement Crimes in Company Positions - Muhammad Nurohim (SEAN Institute, 2026)
The purpose of this research is to identify and analyze the factors causing embezzlement in office positions within companies. This type of research is normative with a legislative approach. The data used are secondary data consisting of primary and secondary legal materials. The research specification used is analytical descriptive. The factors causing embezzlement in office positions within companies are multidimensional, such as economic factors, opportunities arising from the position, and the weakness of the company's internal control system, which also contribute to embezzlement in office positions. The factor of abuse of trust also plays a role in the occurrence of embezzlement in office positions. Weak personal morals and integrity are also a contributing factor. The reasons why someone commits embezzlement in a position can include psychological factors, such as work stress, feeling undervalued, or conflicts with management, which can also influence a person's decision to commit embezzlement. A low understanding of the law and lack of awareness of criminal penalties are also causes of embezzlement in positions. Therefore, it is recommended that members of society refrain from doing it, as it harms both themselves and others.